Pengembangan buku cerita untuk meningkatkan karakter tanggung jawab siswa di sekolah dasar - Lhutfia Wahyu Safutri; Nurul Faizah; Shafina Shafina; Fatahillah Fatahillah (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This study was motivated by the lack of research on instilling discipline character values among 5th grade elementary school students, although this has a significant impact on children's character development. The purpose of this study was to develop a story e-book that can instill discipline values in students. The method used was research and development with the ADDIE model, involving students as participants in product trials. Data were collected through questionnaires to measure the acceptability of the e-book. The results showed that the e-book was well received, with an acceptance percentage reaching 83%. This finding suggests that the use of interactive media in learning can increase student interest and help them understand the importance of discipline. This study concludes that the development of e-books is effective in instilling discipline character.